PENGARUH MOTIVASI BERPRESTASI, IKLIM SEKOLAH, DAN KEPUASAN KERJA TERHADAP KINERJA GURU SMP DI KOMWIL O2 KABUPATEN TEGAL - Noor Choliq (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2013)
The aims of this research are: (1) to analyze influences of motivation for achievement, school climate, and job satisfaction partially toward Junior High School teachers performance in Komwil 02 Tegal Regency; and (2) to analyze the biggest effect factor among motivation for achievement, school climate, and job satisfaction in influencing the teachers performance. In this research, method which be used is survey with Proporsional Cluster Random Sampling. Data collecting method used questionnaire, documentation, and interview. Data analysis technique used double linear regressions. The results of this research showed that motivation for achievement, school climate, and job satisfaction partially gave positive efects to Junior High School teachers performance in Komwil 02 Tegal Regency, and motivation for achievement gave the biggest efect to teachers performance. The implication of this research is that the teacher motivation for achievement should be improved. School climate should be more conducive and job satisfaction should be created. Keywords : Motivation for achievement, school climate, job satisfaction, teachers performance